Nelson's new illustrated Bible dictionary an authoritative one-volume reference work on the Bible, with full-color illustrations - Youngblood, Ronald F.; Bruce, Frederick Fyvie, 1910-1990; Harrison, Roland Kenneth, 1920-1993 (Nashville, TN Nelson, 1995)
Includes bibliographical references, indexes, maps, etc.
First edition published 1986. General editor for first edition, Herbert Lockyer, Sr.
Keywords: Bible -- dictionaries